HUBUNGAN STATUS GIZI, LAMA TIDUR, MASA KERJA DAN BEBAN KERJA DENGAN KELELAHAN KERJA PADA MEKANIK DI PT X PLANT JAKARTA - Estu Triana; Ekawati Ekawati; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Fatigue is a form of body protection mechanism in order to avoid any further damage, and rest is required for body recovery. Fatigue can be influenced by internal and external factors of the worker. PT X Plant Jakarta is a company focuses on remanufacturing heavy equipment components that have a working target for the mechanics. This study aims to analyze the correlation between nutritional status, sleep duration, work period and workload with fatigue at PT X Plant Jakarta. The design of this research is explanatory with cross sectional approach. The population in this study were the mechanics which amounted to 26 peoples using total sampling method. In this study, sleep duration, work period and the fatigue levels were measured by the questionnaire, while nutritional status was measured by IMT measurement, and the workload was measured by Ten Pulse Method. Statistical analysis is using Chi Square with the results showed that variable which is not related fatigue was sleep duration (p value = 0.238), and work period (p value = 1,000). While there are two variables research showed the correlation between fatigue was nutritional status (p value = 0.005), and workload (p value = 0.014). Companies should pay attention to the nutrition of the workers, allow the workers to stretch their muscle stretching